Estudio de factores de transcripción relacionados al estrés salino en plantas de papa (Solanum tuberosum) - Quintana Arrúa, Silverio Andrés (2019)
Solanum tuberosum is the third most important food crop in the world (FAOSTAT, 2009). This crop is moderately sensitive to salinity conditions; in soils with an electrical conductivity (Ec) higher than 5.9 a loss of yield potential of up to 50% is observed. Saline stress involves osmotic and ionic components; an imbalance in the solutes is generated that modifies the K+ / Na+ ratio, thus raising the Na+ concentration in the cytosol. Transient increases in calcium have been reported in response to high salt conditions in numerous studies. Calcium dependent protein kinases (CDPKs) are sensor/transducers of the cation and play a central role in the signaling cascades generated in response to ABA and salt stress. These pathways drastically alter the transcriptome by activating or inhibiting the expression of different genes through the action of transcription factors (TFs). The TFs interact with regulatory elements, which are found in the promoter sequences of the genes. There are more than 80 FT families, of which at least five multigene families, AP2 / EREBP, bZIP, MYB / MYC, NAC, and WRKY can play an important role in the salt /drought stress response.\nThe potato CDPK2 phosphorylates the ABF TF (bZIP family) involved in abiotic stress. In agreement, RT-qPCR assays indicate that StCDPK2 is induced under conditions of salt stress; and in proStCDPK2::GUS plants, promoter activity increases in response to salt. In the laboratory of Dr. Ulloa, transgenic potato plants (cultivar Desiree) that overexpress the isoform StCDPK2, (35S::CDPK2B:6xHis, lines 2B, 2D and 2E) have been generated.\nIn order to identify TFs involved in the saline stress response, a bioinformatic search was performed using the RNAseq database available at the potato genomics resource Spud DB (http://solanaceae.plantbiology.msu.edu/pgsc). This allowed us to select the ERF5, WRKY6, 25K, R2R3 myb, Small heat stress protein and Salt responsive protein 2 (SRP2) genes, whose expression is modified under saline (24 h NaCl) or osmotic (24 h mannitol) conditions versus the control condition. The promoter sequences of the TFs identified were analyzed with the RSAT (Regulatory sequence analysis tools) application. Among others, motifs related to ABA-, light- and auxin- mediated responses were identified; as well as the different TFs that bind to these motifs.\nWe decided to validate the RNAseq data in wild (WT) and transgenic 35S::CDPK2 potato plants grown in vitro for 21 days with 2% sucrose (control) or with the addition of 50 and 150 mM NaCl (salt stress). The biometric data and chlorophyll content were analyzed. The root length of the WT plants was significantly lower than in 2E and 2B plants. In addition, line 2E showed higher stem length than WT. Chlorophyll content was determined in leaves of transgenic and WT plants exposed to 400 mM NaCl; the genetically modified lines presented a higher concentration of total chlorophyll compared to the WT. Based on these data, we analyzed the expression of the selected TFs in WT, 2E and 2B lines exposed to control or saline conditions. In order to perform the RT-qPCR assays, specific oligonucleotides were designed to amplify the partial sequences of the TFs, and the elongation factor 1 alpha (EF-1?) or the Gliceraldehyde-3-phosphate dehydrogenase (GAPDH) genes were used as reference genes when indicated. It was possible to standardize the reaction conditions for WRKY, ERF5 and R2R3 myb. For the 21-day test under control conditions, the expression levels of the TFs were lower in the transgenic plants compared to the WT. Under salinity conditions, we observed changes in the expression of WRKY6 in the WT plants and of R2R3 myb in line 2E.\nIn this work, a first approach was made to study the TFs under salt stress conditions. Our results suggest that their behavior may vary when facing a prolonged period of stress. In addition, bioinformatic, molecular, physiological and biotechnological tools and statistical data analysis were acquired.